Knowledge, Attitudes, and Practices of NICU Doctors and Nurses Toward Prevention and Control of Nosocomial Infection With Multidrug Resistant Organism - Zhou, Jinyan; Chen, Shuohui (Frontiers in Pediatrics, 2022)
Background Nosocomial infection with multidrug resistant organisms (MDRO) can directly influence the curative effect and the prognosis of neonates, bringing great difficulties to clinical treatment. As direct contacts of neonates, the knowledge, attitudes, and practices (KAP) of doctors and nurses are critical for the prevention and control of MDRO infection in neonatal intensive care units (NICUs). Purpose This study describes the KAP of doctors and nurses in NICUs toward the prevention and control of nosocomial infection with MDRO and analyzes its influencing factors. Methods This cross-sectional study used convenience sampling to survey 397 doctors and nurses from the NICU of 28 hospitals in 11 cities in Zhejiang Province, China. A univariate analysis and a multiple linear regression were used to analyze the data. Results The median scoring rate (interquartile range) of the knowledge, attitude, and practice questionnaire was 0.86 (0.82–0.91), 0.98 (0.91–1.00), and 0.995 (0.97–1.00), respectively. However, the median scoring rate regarding “basic knowledge of MDRO” and “special prevention and control measures” was 0.50 in knowledge. The multiple linear regression showed that the influencing factors of KAP were hospital grade, professional title, gender, regular supervision, and training. Conclusions There was still room for improvement in the KAP of NICU doctors and nurses, especially regarding the knowledge. Men, doctors and nurses in Grade II hospitals, and doctors and nurses with primary professional titles had worse KAP. Training and supervision helped improve the KAP. Relevance to Clinical Practice To improve the KAP of doctors and nurses to enhance the prevention and control effect for the MDRO infection in NICUs, hospitals and departments should carry out targeted training and strengthen supervision, while Grade II hospitals, men, and doctors and nurses with primary professional titles need more attention.